Complete Genome Sequence of Salmonella enterica Serovar Enteritidis Myophage Mooltan - Chamblee, Jacob (Microbiol Resour Announc, 2019)
Salmonella enterica serovar Enteritidis is a Gram-negative bacterium and one of the most common foodborne pathogens. Biocontrol using bacteriophage in food products or animals is one possible means by which pathogenic salmonellosis infection could be inhibited. Here, we report the complete genome sequence of the T4-like Salmonella Enteritidis myophage Mooltan.